Differences in the Application of Lateral and Semi-Sitting Labor Positions for Multiparous Maternity Mothers on the Length of Stage II - Uliarta Marbun; Irnawati Irnawati (Sarana Ilmu Indonesia (salnesia), 2023)
Every woman wants her labor to run smoothly and to be able to give birth under normal conditions for both the mother and the baby. However, the desire to have a normal (vaginal) delivery is not an easy thing because many pregnant women feel worried, anxious, and anxious about the delivery process. The goal of normal delivery care is to strive for survival and achieve a high degree of health for both mother and baby through integrated and complete efforts and minimal intervention so that the principles of safety and quality of service can be maintained at an optimal level. The purpose of this study was to find out the difference in the application of semi-sitting and lithotomy positions in multiparous mothers to the length of the second stage at PMB Rismawati. This research was a quantitative study using static group comparison experimental research methods The sample in this study were 30 multiparous mothers. The sampling technique used purposive sampling. The sample in this study was part of the population of multiparous mothers. The results of the man withney test obtained a p-value of 0,370, this value was greater than 0,05 so it can be concluded that there is no difference in the lateral and semi-sitting positions for the duration of the second stage of labor because each position has its own advantages when applied.